Efficacy of pulmonary rehabilitation in patients with chronic obstructive pulmonary disease and obstructive sleep apnea; a randomized controlled trial - Honghua Shen; Yiming Xu; Yin Zhang; Lei Ren; Rui Chen (Medical Journals Sweden, 2024)
Objective: To evaluate the efficacy of pulmonary rehabilitation in the outcomes of patients with chronic obstructive pulmonary disease-obstructive sleep apnoea overlap syndrome patients who used positive airway pressure. Design: Prospective randomized controlled single- blind trial. Patients: A total of 79 patients with chronic obstructive pulmonary disease-obstructive sleep apnoea overlap syndrome were randomly assigned to either the intervention group (n = 40) or control group (n = 39). Methods: All patients consistently adhered to positive airway pressure therapy every night from enrolment in the study, while intervention group patients received additional moderate-intensity aerobic exercise for 20 weeks. Pre- and post-intervention measurements included the 6-Minute Walk Test, Barthel Index, body mass index, fat mass, free fat mass, forced expiratory volume in 1 s (FEV1), FEV1%predicted, modified Medical Research Council, and polysomnography parameters. Results: After 20 weeks, the intervention group exhibited statistically significant improvements in 6MWD, Barthel Index, body mass index, fat mass, and modified Medical Research Council compared with control group (all p < 0.01). In addition, the intervention group showed a significantly lower percentage of total sleep time with oxygen saturation < 90% (p = 0.013) and higher lowest nocturnal oxygen saturation (p = 0.008) than the control group. However, there was no significant difference in FEV1 %predicted between the 2 groups. Conclusion: Pulmonary rehabilitation incorporating moderate-intensity aerobic exercise could improve physical endurance and motor abilities in individuals with chronic obstructive pulmonary disease-obstructive sleep apnoea overlap syndrome, while also improving anamnestic dyspnoea, body composition, and sleep-disordered breathing.